ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PRODUK LAPTOP AXIOO - Tomy Dwi Rizqi (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The development of the times requires every sector in life to always change to keep pace with developments, including the field of information technology which always innovates all the time. Companies compete with each other to be the best and try to make their products a top brand in the eyes of consumers. Consumer satisfaction is a top priority for every company, and is one indicator of the success of a business. One attempt to see which attributes are important to consumers and to what extent the performance of these attributes is through Importance Performance Analysis (IPA). And to determine the level of consumer satisfaction, namely by calculating the consumer satisfaction index or Customer Satisfaction Index (CSI). The object of this research is Axioo Laptop Products (Axioo International Pte Ltd). The data used in the analysis were obtained through filling out questionnaires by consumers as respondents who had bought and used an Axioo Laptop. From the results of this study, a value of 0.7639 or a percentage of 76.39% was obtained, meaning that this number indicated that consumers were satisfied with the performance of the Axioo Laptop.